Toxicity of methanolic crude extracts of azadirachtin against Plutella xylostella (L.) (Lepidoptera: Plutellidae) - Norizan, Nor Shuhaidah (2013)
Leaf mustard is the most popular leaf vegetables in Malaysia, occupying more than 3,000 ha and heavily sprayed with synthetic insecticides against its insect pest Plutella xylostella. The use synthetic insecticides can result resistance problem, residues exceeding the MRL, health hazard to consumers, crops and ecosystem. The use of the botanical insecticides could solve these problems due to their bioactive compounds are fairly complex, making it more difficult for the pest to develop resistance and easily degraded. The toxicity of the methanolic crude extracts Azadirachta excelsa, Melia azedarach and Neem oil against P. xyloxtella was evaluated by leaf dip bioassay using early 3rd instars larvae in the laboratory. A minimum of 6 concentrations (0.75, 1.00, 1.50, 2.00 and 2.50ppm) for each treatment and 6 replications arranged in Randomized Complete Block Design are utilized to obtain the LC50 values for each extracts. The mortality and leaf consumed was recorded at 24, 48 and 72 hours after treatment and the data were subjected to probit analysis. The amount of leaf consumed by the larvae was also measured and the data were subjected to analysis of variance (ANOVA). The methanolic extract of A. excelsa showed the higher toxicity with lower LC50 value of 0.590 ppm and the lowest leave consumed by the larvae compared with M. azedarach (0.794 ppm) and Neem oil (1.716 ppm). Azadirachta excelsa contained an active compound known as Marrangin (azadirachtin L) that are more toxic than azadirachtin A and B in Neem oil and M. azedarach.